The external effects of bank executive pay: Liquidity creation and systemic risk - DeYoung, Robert; Huang, Minjie (Journal of Financial Intermediation, 2021)
We develop a conceptual framework that links the compensation incentives of bank executives to the risk and return externalities generated by banks but borne by society. Using 1994 to 2016 data from large U.S. commercial banks, we find that CEO pay-performance incentives reduce both negative systemic risk externalities and positive liquidity creation externalities, while pay-risk incentives increase both externalities. Our findings offer support for Federal Reserve guidelines that encourage greater reliance on long-term equity-based compensation, and they infer a regulatory tradeoff: Bank executive pay rules aimed at reducing systemic risk will result in reduced system-wide liquidity creation as well.